Chemical Composition of the Essential Oil of Buchenavia tetraphylla Leaves. Issue 1 (2nd January 2017) - Pottier, Maud; Bezerra-Silva, Patrícia Cristina; Bezerra Filhos, Clovis Macêdo; da Silva, Alexandre Gomes; da Silva, Márcia Vanusa; Correia, Maria Tereza dos Santos; Navarro, Daniela Maria do Amaral Ferraz
Abstract: This is a report of chemical composition of Buchenavia tetraphylla essential oil, a neotropical species from Pernambuco state (Brazil). Thirty three components were identified in the essential oil of Buchenavia tetraphylla leaves from Pernambuco state, the major four of which were trans -caryophyllene (9.43%), α-cadinol (10.90%), α-muurolol (14.02%) and trans -cadina-1, 4-diene (17.51%). This essential oil of B. tetraphylla was more complex and richer in composition than that of B. tetraphylla oil from Ceará state. The major compounds in B. tetraphylla from Pernambuco state (α-cadinol and epi -α-muurolol) are not found in the other population. The differences in both essential oils composition may be influenced by several factors but further studies with different populations of B. tetraphylla in various biomes that the species is distributed, are needed to identify possible chemotypes of this species.